Diagnostic utility of movement disorder society criteria for multiple system atrophy - Zhang, Lingyu; Hou, Yanbing; Wei, Qianqian; Ou, Ruwei; Liu, Kuncheng; Lin, Junyu; Yang, Tianmi; Xiao, Yi; Zhao, Bi; Shang, Huifang (Frontiers in Aging Neuroscience, 2023)
Background: The 2008 criterial for the diagnosis of multiple system atrophy (MSA) has been widely used for more than 10 years, but the sensitivity is low, particularly for patients in early stage. Recently, a new MSA diagnostic criteria was developed. Objective: The objective of the study was to assess and compare the diagnostic utility of the new Movement Disorders Society (MDS) MSA criteria with the 2008 MSA criteria. Methods: This study included patients diagnosed with MSA between January 2016 and October 2021. All patients underwent regular face-to-face or telephonic follow-ups every year until October 2022. A total of 587 patients (309 males and 278 females) were retrospectively reviewed to compare the diagnostic accuracy of the MDS MSA criteria to that of the 2008 MSA criteria (determined by the proportion of patients categorized as established or probable MSA). The autopsy is the gold diagnosis standard of MSA, which is not available in clinical practice. Thus, we applied the 2008 MSA criteria at the last review as the reference standard. Results: The sensitivity of MDS MSA criteria (93.2%, 95% CI = 90.5-95.2%) was significantly higher than that of 2008 MSA criteria (83.5%, 95% CI = 79.8-86.6%) (P<0.001). Additionally, the sensitivity of MDS MSA criteria was maintained robust across different subgroups, defined by diagnostic subtype, disease duration, and symptom of onset. Importantly, the specificities were not significantly different between MDS MSA criteria and 2008 MSA criteria (P>0.05). Conclusion: The present study demonstrated that the MDS MSA criteria exhibited good diagnostic utility for MSA. The new MDS MSA criteria should be considered as useful diagnostic tools for clinical practice and future therapeutic trials.